2011
DOI: 10.3389/fimmu.2011.00062
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in Injured Skeletal Muscle: A Perpetuum Mobile Causing and Limiting Fibrosis, Prompting or Restricting Resolution and Regeneration

Abstract: Macrophages are present in regenerating skeletal muscles and participate in the repair process. This is due to a unique feature of macrophages, i.e., their ability to perceive signals heralding ongoing tissue injury and to broadcast the news to cells suited at regenerating the tissue such as stem and progenitor cells. Macrophages play a complex role in the skeletal muscle, probably conveying information on the pattern of healing which is appropriate to ensure an effective healing of the tissue, yielding novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 162 publications
3
60
0
3
Order By: Relevance
“…Exercise increases muscle mass, in part, through activation of macrophages. 34,35 The type of macrophage involved in the macrophage response depends on their function. M1 killer macrophages are involved in phagocytosis or meeting a microbe challenge, which leads to a sustained inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise increases muscle mass, in part, through activation of macrophages. 34,35 The type of macrophage involved in the macrophage response depends on their function. M1 killer macrophages are involved in phagocytosis or meeting a microbe challenge, which leads to a sustained inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle stem cells fail to activate their regenerative potential in the absence of the inflammatory response. 66,70,74 The release of DAMPs/alarmins as a consequence of cell death and of immune cell activation might be important in the reciprocal activation/regulation of immune and of muscle stem/progenitor cells. The availability of novel elegant genetic inducible cell-fate mapping models will be valuable for the better understanding of the overall scenario.…”
Section: The Regeneration Of Injured Muscles Depends On Inflammationmentioning
confidence: 99%
“…Their depletion results in the persistence of cell remnants, deriving either from necrotic fibers, dying progenitor cells or inflammatory leukocytes. Moreover, upon depletion of macrophages muscle regeneration is severely compromised (reviewed in Bosurgi et al 70 and Tidballand and Villalta 71 ). Macrophages and muscle regeneration are therefore closely associated.…”
Section: The Predators: Macrophages Scavenge Muscle Debrismentioning
confidence: 99%
“…Keeling et al (25) further reported that M-CSF-induced macrophage differentiation stimulated the increase of nuclear number and myotube elongation in C2C12 cells. These results clearly indicate the beneficial effects of macrophages during the response to muscle injury, although detrimental actions of macrophages are also reported (5,56,57), suggesting the divergent roles of macrophages.…”
Section: Responses To Reloadingmentioning
confidence: 73%